Nasionalisme Dan Identitas Muslim (Telaah Aksiologi Pendidikan Islam) - Napitupulu, Dedi Sahputra (Ta'allum: Jurnal Pendidikan Islam, 2019)
Nationalism and muslim identity is a typical character that belongs to the nation of Indonesia, although both are different in substance but have in common the principle, nationalism is the consciousness of a nation that has then gave birth to feelings of love towards the motherland. While the muslim identity is practised Islamic teachings and culture of Islam which was later arrested as a muslim identity. By using the method of the study the research library produces a correlation between nationalism and muslim identity. If seen through the eyes of axiology of education Islamic glass. Delivering the country's population of nationalism being loving his homeland and therefore surely he would feel comfortable living in his country. Similarly, Muslim identity or expression of Islam practised impressed different, but in the end had the same purpose, namely to practice God's commands and away from the restriction, which will ultimately deliver mankind to happiness in world and in the hereafter.